An iterative modeling technique for the two-phase eight winding hybrid stepper motor for the calculation of instantaneous torque including magnetic saturation - Limcangco, Naomi O. (2000)
An iterative model for the two phase eight winding hybrid stepper motor has been derived. The new model includes three magnetic effects - magnetic saturation, detent torque and variable reluctance. It was then used to find the instantaneous torque profile using ideal conditions. The simulated torque was compared in form with an experimentally determined torque profile and was found to conform (to a certain degree) with the empirical torque.